The Existence of Marriage Agreement Registration In Legal Protection Perspective - Latifani, Soraya Ulfa; Ali, Moh.; Rato, Dominikus (PT Matra Cendikia Abadi, 2024)
Failure to comply with the registration of the marriage agreement causes the agreement to be null and void because it does not fulfill one of the conditions for a valid agreement according to Article 1320 of the Civil Code and is contrary to Article 29 paragraph (1) of Law no. Therefore, this research will write about the role of registration of marriage agreements in ensuring legal certainty and protection of the rights of the parties concerned and the legal consequences of non-compliance in registering marriage agreements. The type of research used is a normative juridical method, namely research guided by positive legal regulations in accordance with the laws and regulations applicable in society. In resolving a legal issue, the author uses two approaches, namely the Statute Approach which is carried out by examining all statutory regulations relating to the legal issue to be studied, and the Conceptual Approach which carries out the interpretation. principles, laws and legal concepts according to the legal issue being studied. The legal materials used are primary legal materials and secondary legal materials using the library research method of collecting legal materials (Library Research) with research analysis using deductive methods. The result is registration of a marriage agreement has permanent legal force, thereby providing optimal protection for both parties from potential disputes in the future. Failure to comply with the obligation to register a marriage agreement, even though it has been made in the form of an authentic deed by a notary, has the implication that the agreement is null and void. It is hoped that in the future the government can increase outreach and education as well as simplify the procedures for registering marriage agreements. Keywords: Marriage Agreements; Register; Legal Protection.